2015
DOI: 10.32607/20758251-2015-7-2-57-63
|View full text |Cite
|
Sign up to set email alerts
|

Search for Human Lactate Dehydrogenase A Inhibitors Using Structure-Based Modeling

Abstract: The human lactate dehydrogenase isoform A plays an important role in the anaerobic metabolism of tumour cells and therefore constitutes an attractive target in the oncology field. Full-atom models of lactate dehydrogenase A (in complex with NADH and in the apo form) have been generated to enable structure-based design of novel inhibitors competing with pyruvate and NADH. The structural criteria for the selection of potential inhibitors were established, and virtual screening of a library of low-molecular-weigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…1C). The concentration at which PSTMB inhibits LDHA activity (IC 50 = 145.2 nM) was much lower than that of oxamate (IC 50 = 130.6 μM), a standard inhibitor of LDHA 1820 .
Figure 1PSTMB has a potent inhibitory effect on in vitro LDHA activity. ( A ) Structures of the selenobenzene compounds analyzed in this study are shown.
…”
Section: Resultsmentioning
confidence: 97%
“…1C). The concentration at which PSTMB inhibits LDHA activity (IC 50 = 145.2 nM) was much lower than that of oxamate (IC 50 = 130.6 μM), a standard inhibitor of LDHA 1820 .
Figure 1PSTMB has a potent inhibitory effect on in vitro LDHA activity. ( A ) Structures of the selenobenzene compounds analyzed in this study are shown.
…”
Section: Resultsmentioning
confidence: 97%
“…The IC 50 value was determined to be 1.2 mM. Interestingly, inhibitor 4 binds in a similar manner to the earlier investigated oxamate derivative STK381370 (ΔGcalc = –7.9 kcal/mol, IC 50 5 mM) [24], forming additional interactions with the loop 96–111. However, the interaction of 4 is more efficient.…”
Section: Resultsmentioning
confidence: 60%
“…This rule defines the ranges of physicochemical parameters associated with molecule fragments (molecular weight < 300, log P ≤ 3, hydrogen bond donors ≤ 3, hydrogen bond acceptors ≤ 3, and rotatable bonds ≤ 3). Molecular docking of compounds from the obtained focused library was performed using Lead Finder 1.1.15 in the “extra precision” mode [29, 30] and the models of human LDH-A (with and without the bound molecule of NADH) constructed in our previous work [24]. At the first step of the selection of inhibitors, some compounds were eliminated when the distance between the sulfur of the sulfo group and the guanidinium carbon of Arg168 at their binding with LDH-A exceeded 5.5 A.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To alter the catalytic properties of an enzyme random mutations are introduced into the structure of the active site [71]. Similarly, the majority of the developed drugs bind to functional centers of proteins (see [72] as an example). Practical application of allosteric sites is arguably rare, although some examples are known.…”
Section: Binding Sites In Biotechnology and Biomedicinementioning
confidence: 99%